Addressing today's challenges in automotive remanufacturing - Robert Casper; Erik Sundin (Journal of Remanufacturing, 2018)
Automotive remanufacturing companies are nowadays facing a wide range of challenges. Typical challenges from the point of view of suppliers, producers and customers. Several process steps are analysed and problem fields are dissected: From the core management, to disassembly and cleaning to machining and testing. The main fields of challenges analysed in this paper are: the vagueness in respect of fiscal value, environmental regulations and taxation of core parts, the important need for a continuing qualification of staff and engineers, an efficient core management, the adaption of pricing models and the competence to handle the growing variety and complexity. The focus of this analysis lies on activities of the independent after-market (IAM) for remanufactured products.
Keywords: 650; Remanufacturing; Automotive; Mechatronics; Electronics; Design for Remanufacturing; Core management; Circular economy